A Proposed Model for Employee Competencies in Hospitality 4.0 Talent Management: H4TM - ESENDEMIRLI, Ebru; OZTURKOGLU, Yücel; SARI, Ferika Ozer (International Journal of Contemporary Economics and Administrative Sciences, 2024)
Purpose of this study is to specify and prioritize the employee competencies in the context of key specialist jobs in lodging industry and to introduce a model as “Hospitality 4.0 Talent Management”. This study integrates the qualitative and quantitative approaches. To evaluate the performance of Talent Management with Hospitality 4.0 perspective, the valid and reliable criteria are determined by a literature review. Next stage was to find out the weight and importance of each identified dimension, by use of Best- Worst- Method (BWM). As a result, a novel model is proposed to help lodging organizations to specify and prioritize their key employees’ competencies in terms of hard, soft and mixed skills for H4TM, thus to map their post Covid -19 talent management practices effectively.